Arsenene/Ca(OH)2 van der Waals heterostructure: strain tunable electronic and photocatalytic properties. Issue 70 (15th September 2017) - Li, Xiao-Hua; Wang, Bao-Ji; Cai, Xiao-Lin; Yu, Wei-Yang; Zhang, Li-Wei; Wang, Guo-Dong; Ke, San-Huang
Abstract : Based on ab initio calculations, we identify that the arsenene/Ca(OH)2 van der Waals heterostructure is an indirect-band-gap semiconductor and find that its electronic and photocatalytic properties can be continuously tuned by external strain. Abstract : Vertical stacking of two-dimensional materials has recently emerged as an exciting method for the design of novel electronic and optoelectronic devices. In this work, we investigate the structural, electronic, and potential photocatalytic properties of arsenene/Ca(OH)2 van der Waals (vdW) heterostructures using first-principles calculations. It is found that all of the heterostructures are semiconductors with indirect band gaps and present similar electronic properties, almost irrespective of the stacking arrangement. However, among these heterostructures, the β-stacking heterostructure is found to be the most stable and its band gap and band edge position can be tuned by biaxial strain. In particular, comparing the band edge positions with the redox potentials of water shows that the strained β-stacking arsenene/Ca(OH)2 vdW heterostructure is a potential photocatalyst for water splitting. Meanwhile, this heterostructure exhibits significantly improved photocatalytic properties under visible-light irradiation by the calculated optical absorption spectra. Our findings provide a detailed understanding of the physical properties of arsenene/Ca(OH)2 vdW heterostructures and a new way to improve the design of photocatalysts for water splitting.